Effect of Tai Chi on Quality of Life, Body Mass Index, and Waist-Hip Ratio in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Qin, Jiawei; Chen, Yannan; Guo, Shuai; You, Yue; Xu, Ying; Wu, Jingsong; Liu, Zhizhen; Huang, Jia; Chen, Lidian; Tao, Jing (Frontiers in Endocrinology, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a worldwide public health concern with high morbidity and various progressive diabetes complications that result in serious economic expenditure and social burden. This systematic review aims to evaluate the effect of Tai Chi on improving quality of life (QoL), body mass index (BMI) and waist-hip ratio (WHR) in patients with T2DM. Method: A systematic review and meta-analysis was performed following PRISMA recommendation. Four English databases and three Chinese databases were searched. The PEDro scale was used to assess the methodological quality of including studies. Study inclusion criteria: randomized controlled trials (RCTs) and quasi-experimental studies were included, patients with T2DM that adopted Tai Chi as intervention and QoL, BMI and/or WHR as outcome measurements. Results: Eighteen trials were included. The aggregated results of seven trials showed that Tai Chi statistically significantly improved QoL measured by the SF-36 on every domains (physical function: MD = 7.73, 95% confidence interval (CI) = 1.76 to 13.71, p = 0.01; role-physical function: MD = 9.76, 95% CI = 6.05 to 13.47, p < 0.001; body pain: MD = 8.49, 95% CI = 1.18 to 15.8, p = 0.02; general health: MD = 9.80, 95% CI = 5.77 to 13.82, p < 0.001; vitality: MD = 6.70, 95% CI = 0.45 to 12.94, p = 0.04; social function: MD = 9.1, 95% CI = 4.75 to 13.45, p < 0.001; role-emotional function: MD = 7.88, 95% CI = 4.03 to 11.72, p < 0.001; mental health: MD = 5.62, 95% CI = 1.57 to 9.67, p = 0.006) and BMI (MD = -1.53, 95% CI = -2.71 to -0.36, p < 0.001) compared with control group (wait list; no intervention; usual care; sham exercise). Conclusion: Tai Chi could improve QoL and decrease BMI for patients with T2DM, more studies are needed to be conducted in accordance with the suggestions mentioned in this review.